Correlation Between Ultrasonographical and Cytopathological Features of Thyroid Nodules - Huma Khaliq, Saima Gulzar, Khurram Shehzad, Koukab Gulzar, Nagina Khaliq, Sehrish Afzal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Thyroid nodule is a common presentation in the head neck clinics as well as radiological departments. For the accurate assessment and identification of a thyroid nodule the correlation between ultrasonographical and cytological examination is a preferable protocol. Objective: To evaluate the correlation between ultrasonographic and cytopathologic features of thyroid nodules. Methodology: This cross-sectional study was conducted at Department of Radiology, Nori Hospital Islamabad from 1st December 2018 to 30th June 2019. A total of 150 patients from both genders were included in this study. The patients within the age group of 25-60 years were included. Known cases of thyroidal malignancy or other carcinoma, previously treated patients and pediatric patients were excluded. The cytological examination Fine needle aspiration cytology was requested to all these patients in addition to complete ultrasonographical Doppler based imaging. The TIRADS classification for ultrasonographical assessment in correlation with cytological classification through Bethesda was adapted for thyroid nodule identification. Results: There were 83.3% females and 16.6% males with the mean age of 40.1±6.7 years. Within the various ultrasound related features it was observed that majority of the cases were having higher number of positivity for composition as well as vascularity while there were 142 cases out of 150 cases having negative results for shape overall accuracy revealed that the feature of nodule composition demonstrated the highest sensitivity. In contrast, the shape of the nodule exhibited the highest specificity (96.2%), diagnostic accuracy (88.9%) was seen. 84% cases were benign while 16% were malignant. A significant of benign cases of TIRADS 2 were majorly reported in the TIRADS 5 followed by 4. The majority of the patients were TIRADS 2 and Bethesda 2 classification and benign. There were 24 cases as 16% cases were malignant with highest number of cases within the TIRADS 5 and Bethesda 5 smear. There were 90% of the patients identified with papillary thyroid carcinoma while 10% were suffering from follicular carcinoma. Conclusion: The application of TIRADS classification based on ultrasongrphical results is highly significant in bringing accuracy to the cytopathological results and also reducing unnecessary fine needle aspiration cytology. Keywords: Correlation, Ultrasound, Cytopathology, Thyroid nodules, Thyroid Imaging Reporting and Data System (TIRADS)